ESTABLISHMENT AND DEVELOPMENT OF THE TECHNICAL REGULATION SYSTEM IN THE EU - Myrna, Nadiya; Sokolova , Viktoriya (Pressing Problems of Public Administration, 2021)
The article analyzes the formation and development of the technical regulation system on the example of the European Union. The historical stages of construction and formation of the system of technical regulation in Europe are considered. The impact of the technical regulation system on the development and creation of the EU internal market is determined separately. Four stages of construction of a modern system of technical regulation in the EU are singled out.To date, the most effective model of the system of technical regulation in the framework of international cooperation is considered to be the European one. It is designed to provide a single assessment of the conformity of goods, processes and services in the context of interaction not only in the EU internal market but also in the markets of other countries.Cooperation between Ukraine and the EU in the field of technical regulation aims at approximating legal framework of Ukraine in the field of technical regulation to the EU and WTO requirements, including the transition from mandatory certification to conformity assessment, adoption of technical regulations in line with EU New Approach Directives, revision and replacement of old standards (GOST) and introduction of ISO (International Organization for Standardization) and European standards, launching a market surveillance system, updating and modernizing material base, reforming and strengthening institutional base of quality assurance, etc.A tangible result of this cooperation should soon be seen in signing the Agreement on Conformity Assessment and Mutual Acceptance of Industrial Products (ACAA Agreement) between EU and Ukraine in key sectors of production.